2007
DOI: 10.1038/modpathol.3800714
|View full text |Cite
|
Sign up to set email alerts
|

Intramucosal gastric adenocarcinoma of poorly differentiated type in the young is characterized by Helicobacter pylori infection and antral lymphoid hyperplasia

Abstract: The aim of this investigation was to clarify the histological characteristics of gastric cancer in the young. Twenty-three surgically resected specimens of young patients (under 30 years of age; young group) with intramucosal cancer of poorly differentiated type and 42 surgically resected specimens of elderly patients (more than 40 years of age; elderly group) with tumors of the identical depth and histological type were examined. The degree of gastritis and Helicobacter pylori (H. pylori) infection was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
3
25
0
2
Order By: Relevance
“…Helicobacter pylori infection is strongly related to the development of gastric cancer in young patients [10, 11, 20, 21]. In the current study, younger patients showed a statistically significant higher risk of having H. pylori infection and the diffuse histological type of gastric carcinoma after multivariate analysis.…”
Section: Discussionsupporting
confidence: 48%
“…Helicobacter pylori infection is strongly related to the development of gastric cancer in young patients [10, 11, 20, 21]. In the current study, younger patients showed a statistically significant higher risk of having H. pylori infection and the diffuse histological type of gastric carcinoma after multivariate analysis.…”
Section: Discussionsupporting
confidence: 48%
“…As found in similar patient populations, the number of females was significantly higher in our young patient group compared to the older patients ( P < 0.01). In both groups, a large number of the lesions were located in the middle part of the stomach, with a median size of 3.8–3.9 cm.…”
Section: Methodssupporting
confidence: 84%
“…It should be noted that the accumulation of 8OHdG was already increased not only in the noncancerous mucosal neck cells but also in the noncancerous foveolar epithelial cells in both our young and older patients groups. H. pylori ‐induced chronic superficial gastritis (i.e., ‘nodular gastritis’) is accompanied and is associated with carcinogenesis in young patients . In contrast, older patients with gastric cancer generally have chronic atrophic gastritis .…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, the International Agency for Research on Cancer (IARC) accepted H. pylori as a definite carcinogen (group 1) that induces gastric carcinomas. Recently, the close relationship between H. pylori infection and the development of undifferentiated-type carcinomas has been demonstrated [11][12][13].…”
Section: Introductionmentioning
confidence: 99%